POWER QUALITY ENHANCEMENT IN ARC FURNACE ENVIRONMENT - Nupur Laxman Mali; Dr. V. N. Kalkhambkar; Abhijeet Shete (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Electrical power quality defines the health of power system which includes voltage and current quality, a reliability of power supply and maintaining sinusoidal nature of waveform. Voltage flickers and fluctuations, poor power factor and harmonics are the most common power quality issues in steel producing plants because of it contains Electric Arc Furnace (EAF), electrical drives and welding machines. Non-linear characteristics of EAF are the major source of power quality issues that include reactive power consumption, harmonic production and system unbalance. Static VAr compensator (SVC) is one of the efficient FACTS devices to overcome these power quality problems. In this paper, Operating principle and control strategy of Thyristor Controlled Reactor - Fixed Capacitor (TCR-FC) are described briefly. TCR-FC type of SVC is used in proposed work for reactive power compensation, reduction of voltage fluctuations and harmonic mitigation. The SVC model is simulated in MATLAB software and results are observed